THE CARDIAC BIOMARKER, NT-PRO BNP, AND HEMODYNAMIC PARAMETER, PCWP IN PATIENTS UNDERGOING ON-PUMP CABG SURGERY - GURPREET SINGH OBEROI; RAJWINDER KAUR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: This study aimed to investigate the correlation between preoperative N-terminal pro-brain natriuretic peptide (NT-proBNP) levels and intraoperative pulmonary capillary wedge pressure (PCWP) in patients undergoing on-pump coronary artery bypass grafting (CABG). Methods: Pre-operative blood samples were collected to assess NT-proBNP levels. During surgery, PCWP and other hemodynamic parameters were measured using a Swan-Ganz catheter. Plasma dobutamine levels were evaluated 4 h post-incision. Statistical analysis was performed to identify correlations between biomarkers and hemodynamic data. Results: Pre-operative NT-proBNP levels demonstrated a strong correlation with intraoperative PCWP (r=−0.84, p<0.05), suggesting its potential as a predictor for low cardiac output syndrome. Conclusion: NT-proBNP emerges as a valuable biomarker for identifying patients at risk of hemodynamic instability during on-pump CABG procedures. Continuous monitoring of NT-proBNP and PCWP could facilitate risk assessment and improve intraoperative care.